Knowledge of obstetric danger signs among recently-delivered women in Chamwino district, Tanzania: a cross-sectional study - Deogratius Bintabara; Rose N. M. Mpembeni; Ahmed Abade Mohamed (BMC, 2017)
Abstract Background Low knowledge of danger signs has been shown to delay seeking obstetric care which leads to high maternal mortality and morbidity worldwide. In Tanzania about half of pregnant women are informed about obstetric danger signs during antenatal care, but the proportion of those who have full knowledge of these obstetric danger signs is not known. This study assessed the knowledge of obstetric danger signs and its associated factors among recently-delivered women in Chamwino District, Tanzania. Methods A community-based cross-sectional study was conducted in January 2014 in Chamwino District, Tanzania. A woman was considered knowledgeable if she spontaneously mentioned at least five danger signs in any of the three phases of childbirth (pregnancy, childbirth and postpartum) with at least one in each phase. Multistage cluster sampling was used to recruit study participants. Descriptive and bivariate analyses were conducted. Multivariable logistic regression analyses were performed to control for confounding and other important covariates. Results A total of 428 women were interviewed. The median age (IQR) was 26.5 (22-33) years. Only 25.2% of respondents were knowledgeable about obstetric danger signs during pregnancy, childbirth/labour and postpartum. Significant explanatory variables of being knowledgeable about obstetric danger signs were found to be maternal education (AOR = 1.96; 95% CI: 1.01, 3.82), maternal occupation (AOR = 2.23; 95% CI; 1.10, 4.52), spouse occupation (AOR = 2.10; 95% CI: 1.02, 4.32) and counseling on danger signs (AOR = 3.42; 95% CI: 1.36, 8.62) after controlling for the clustering effect, confounding and important covariates. Conclusion A low proportion of women was found to be knowledgeable about obstetric danger signs in Chamwino district. Therefore, we recommend the Ministry of Health to design and distribute the maternal health booklets that highlight the obstetric danger signs, and encourage antenatal care providers and community health workers to provide frequent health education about these danger signs for every pregnant woman in order to increase their level of knowledge about obstetric danger signs.